Increasing Knowledge of Family Empowerment and Welfare Mothers (PKK) about Herbal Medicine - Raden Roro Dewi Rahmawaty Aktyani Putri; Thatit Nurmawati; Anita Rahmawati (STIKes Patria Husada Blitar, 2023)
The trend towards a more natural lifestyle encourages people to choose herbal medicines cause not to significant side effects and usually have more affordable prices through utilize traditional ingredients to maintain health. However, many housewives in rural areas do not understand that herbal plants are not only very useful for seasoning dishes, but these plants are also widely needed to cure various diseases. This study aimed to reveal the effect of health education about the use of herbal plants as family medicine on increasing the knowledge of Family Empowerment and Welfare Mothers (PKK) Mojorejo Village, Wates District, Blitar Regency. The research design used quasy-experimental with a one-group pre-test post-test design without control group. The population and sample in this study were mothers of Family Empowerment and Welfare (PKK) Mojorejo Village, Wates District, Blitar Regency totaling 28 respondent taken by total sampling. The data were analyzed by the Wilcoxon Signed Rank Test. The results showed that there was a difference in the average score of knowledge before and after being given health education, namely 20.21 and 28.14. There was a significant influence the provision of education on the knowledge and skills about the use of herbal plants as family medicine of Family Empowerment and Welfare Mothers (PKK) Mojorejo Village, Wates District, Blitar Regency.